Foods of Non-Animal Origin Chemistry, Technology, Inspection Procedures - Bhagat, Arpan; Caruso, Giorgia; Micali, Maria; Parisi, Salvatore (Chemistry of Foods, 2016)
This Brief discusses aspects of the increasingly complex production of legal and reliable food products of non-animal origin.  It introduces to the Food Safety Modernization Act (FSMA) in the USA (from January 2011), which requires the food industry to follow risk-based approaches with stronger self-regulation of food safety through measures such as the foreign supplier verification programs (FSVPs). The Brief addresses important chemical hazards of vegetable products: their peculiar microbial ecology, that can become responsible for the occurrence of specific foodborne disease outbreaks, and the chemistry of the involved neurotoxins and other dangerous molecules, that can potentially lead to lethal pathological reactions. Finally, the Brief also critically discusses the technology of ready-to-eat vegetable products and chemical and physical modifications used for packed products (respiration of vegetables, colorimetric modifications, etc.).